Optimalisasi Pemanfaatan Digitalisasi Keuangan UKM Melalui Aplikasi SiApik di Desa Sugihan, Kecamatan Tengaran, Kabupaten Semarang - Myra Andriana; Tantik Sumarlin; Dewi Widyaningsih; Arie Atwa Magriyanti; Reni Veliyanti; Puteri Anindya Maulan; Dwi Astutik; Ratnaningrum; Heni Susilowati; Titin Hargyatni; Pemilia Sulistyowati; Zahra Dinul Khaq (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The activities of MSME actors are not only carrying out business activities, but are also required to make financial reports to evaluate the development of their business. However, the lack of knowledge of financial management such as accounting records and difficulty in using accounting applications are common obstacles. To overcome this, the community service team in collaboration with the University of Computer Science and Technology and STIE Modern Economic Studies held a digital-based financial management training program by utilizing the SIAPIK application developed by Bank Indonesia. This activity involves theoretical and practical training methods, intensive mentoring, and discussions and evaluations through collecting feedback data to assess participants' abilities in completing basic financial recording tasks. The impact is that MSMEs in Sugihan Village have become more skilled in preparing digital financial reports using the application, thereby increasing the transparency and effectiveness of business financial management.